Some fixed point theorems in b2-metric spaces - Kumam, Poom; Mitrović, Zoran D.; Pavlović, Mirjana V. (Vojnotehnički glasnik / Military Technical Courier, 2019)
In this paper, we first prove a result that gives a sufficient condition for the convergence of the sequences in the  b2-metric space. Next, we give some fixed point theorems in the  b2-metric space. Some of our results are the corresponding generalizations of the known results in the  b2-metric space, which is confirmed by  some examples.
Keywords: fixed points; common fixed points; 2-metric space; b2-metric space